ANALISIS KUALITAS TERJEMAHAN PADA LAMAN WEB KBRI BEIJING - Sofie Sofie; Niza Ayuningtias (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to evaluate the accuracy of the Indonesian to Mandarin translation of a web page from the Indonesian Embassy in Beijing. The Nababan translation quality evaluation methodology, which was used in this study, divides translation product quality into three categories: accuracy, acceptability, and readability. This study has two objectives: 1) to analyze the level of accuracy, acceptability and readability of the Indonesian Embassy in Beijing's website and 2) to describe the quality of the translation of the Indonesian Embassy's website in Beijing. The text, which was broken up into 37 pieces of data, was sent to a competent rater to evaluate. The results revealed that the Indonesian Embassy in Beijing's website translation was of lower accuracy, acceptable quality, and had a moderate degree of readability, scoring an overall 2.48 out of 3 for correctness, acceptability, and readability. Although there are certain terms in the target text that require more than one reading to fully get the meaning, the target text is widely accepted and fairly simple for readers who are native speakers of it. It can be concluded that the content of the source text is not conveyed accurately to the target text